Impact of Immune Response in Short-term and Long-term Outcomes After Minimally Invasive Surgery for Colorectal Liver Metastases: Results From a Randomized Study. Issue 6 (December 2021) - Lopez-Lopez, Victor; Gómez Ruiz, Alvaro; Pelegrin, Pablo; Abellán, Beatriz; Lopez-Conesa, Asunción; Brusadin, Roberto; Cayuela, Valentin; García, Ana; Robles Campos, Ricardo
Abstract : Background: The potential benefit related to laparoscopic liver surgery (LLS) for colorectal liver metastases outcomes is not well known. Materials and Methods: Serum cytokines associated with Th1 (tumor necrosis factor-α) and Th2 [interleukin (IL)-10 and IL-6] phenotypes were measured in 36 patients operated on for colorectal liver metastases by open liver surgery (OLS) and LLS. Measurements were performed at 3 time points: 1 day before surgery, day 3 postoperative, and 1 month postoperative. We compared the postoperative inflammatory response influence between LLS and OLS on long-term outcomes. Results: In both groups, only IL-6 levels on day 3 postoperative were higher than those measured preoperatively and at 1 month. Comparing the tumor necrosis factor-α levels between the LLS and OLS groups, preoperative (7.28 vs. 2.36), day 3 (7.99 vs. 4.08) and 1 month (7.39 vs. 1.99) postoperative levels were higher in the OLS group ( P <0.01, <0.01, and <0.01, respectively). In contrast, IL-10 levels were higher in the LLS group preoperatively (7.51 vs. 4.57) and on day 3 postoperative (13.40 vs. 4.57) ( P =0.03 and 0.01, respectively). A cut-off IL-6 level of ≥4.41 in the first month was associated with a higher risk of recurrence (logrank=4.8, P =0.02). Conclusions: Both LLS and OLS induce an initial increase in IL-6 that normalizes one month after surgery, showing a similar pattern. In addition, a cut-off IL-6 value of 4.41 pg/mL was established, with a higher concentration at 1 month postoperative possibly related to a higher risk or recurrence.